2010
DOI: 10.1029/2009jc005330
|View full text |Cite
|
Sign up to set email alerts
|

CO2 fluxes across the air‐sea interface in the southeastern Beaufort Sea: Ice‐free period

Abstract: [1] Surface mixed layer CO 2 fugacities (fCO 2 -sw) calculated from carbonate system parameters in the southeastern Beaufort Sea during the ice-free period ranged from 240 to 350 matm in fall 2003 and from 175 to 515 matm in summer 2004. The surface mixed layer remains mostly undersaturated with respect to atmospheric CO 2 (378 matm) and, therefore, acts as a potential CO 2 sink throughout this period. Air-sea CO 2 fluxes (FCO 2 ) were first computed assuming ice-free conditions and ranged from −32.4 to +8.6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 105 publications
10
80
1
Order By: Relevance
“…The surface waters of Amundsen Gulf were weakly undersaturated with respect to atmospheric CO 2 throughout the year. Hence, during the open-water months, the region acted as a moderate sink for atmospheric CO 2 , as reported by Mucci et al (2010), but these inputs made only a minor contribution to the monthly changes in surface DIC. Biological processes thus made up the balance of the observed monthly changes in surface DIC and TA.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The surface waters of Amundsen Gulf were weakly undersaturated with respect to atmospheric CO 2 throughout the year. Hence, during the open-water months, the region acted as a moderate sink for atmospheric CO 2 , as reported by Mucci et al (2010), but these inputs made only a minor contribution to the monthly changes in surface DIC. Biological processes thus made up the balance of the observed monthly changes in surface DIC and TA.…”
Section: Resultsmentioning
confidence: 82%
“…Carbon losses due to burial in the sediments, at a depth of 350-380 m, thus account for a small percentage of primary production, and were assumed negligible over the annual time scale of interest (Mucci et al 2008). Furthermore, it has been shown that sedimentation rates in Amundsen Gulf are very low (Macdonald et al 1998;Richerol et al 2008).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent findings point to significant CO 2 fluxes through sea ice [Delille, 2006;Nomura et al, 2010]. At this stage, observations suggest that the sea ice zone could be a source of atmospheric CO 2 in winter [Miller et al, 2011b], and a sink in summer and fall [Else et al, 2008;Mucci et al, 2010], with a transition period in between Nomura et al, 2010], and a net uptake from the sea ice zone on an annual basis [Rysgaard et al, 2011].…”
Section: Inorganic Carbon Dynamicsmentioning
confidence: 99%